"Primer registro de hojas de Malvaceae en el Neogeno de Argentina y Brasil" (Ameghiniana, 2014)
"The new genustvuüoaciphultum Anzótegui is erected with two species: Malvaciphyllum quenquiadensis Anzótegui sp. nov.,from the Upper Miocene of the San José Formation in northwestern Argentina (Tucumán province) andMalvacip/¡yllll/1l sp. from the Pliocene of the ""camadas de Nova Iorque"" in the State of Maranhao, Brazil.The lea ves were compared with living members of Malvaceae."